Tracing the migration of mantle CO2 in gas fields and mineral water springs in south-east Australia using noble gas and stable isotopes. (15th August 2019) - Karolytė, Rūta; Johnson, Gareth; Györe, Domokos; Serno, Sascha; Flude, Stephanie; Stuart, Finlay M.; Chivas, Allan R.; Boyce, Adrian; Gilfillan, Stuart M.V.
Abstract: Geochemical monitoring of CO2 storage requires understanding of both innate and introduced fluids in the crust as well as the subsurface processes that can change the geochemical fingerprint of CO2 during injection, storage and any subsequent migration. Here, we analyse a natural analogue of CO2 storage, migration and leakage to the atmosphere, using noble gas and stable isotopes to constrain the effect of these processes on the geochemical fingerprint of the CO2 . We present the most comprehensive evidence to date for mantle-sourced CO2 in south-east Australia, including well gas and CO2 -rich mineral spring samples from the Otway Basin and Central Victorian Highlands (CVH). 3 He/ 4 He ratios in well gases and CO2 springs range from 1.21 to 3.07 RA and 1.23–3.65 RC /RA, respectively. We present chemical fractionation models to explain the observed range of 3 He/ 4 He ratios, He, Ne, Ar, Kr, Xe concentrations and δ 13 C(CO2 ) values in the springs and the well gases. The variability of 3 He/ 4 He in the well gases is controlled by the gas residence time in the reservoir and associated radiogenic 4 He accumulation. 3 He/ 4 He in CO2 springs decrease away from the main mantle fluid supply conduit. We identify one main pathway for CO2 supply to the surface in the CVH, located near a major fault zone. Solubility fractionation during phase separation is proposed to explain the range in noble gas concentrations and δ 13 C(CO2 ) values measured in the mineral spring samples. This process is also responsible for low 3 He concentrations and associated high CO2 / 3 He, which are commonly interpreted as evidence for mixing with crustal CO2 . The elevated CO2 / 3 He can be explained solely by solubility fractionation without the need to invoke other CO2 sources. The noble gases in the springs and well gases can be traced back to a single end-member which has suffered varying degrees of radiogenic helium accumulation and late stage degassing. This work shows that combined stable and noble gas isotopes in natural gases provide a robust tool for identifying the migration of injected CO2 to the shallow subsurface.